Modulation of histamine-induced bronchoconstriction with inhaled, oral, and intravenous clemastine in normal and asthmatic subjects. Issue 10 (October 1981) - Hartmann, V; Magnussen, H; Holle, J P; Schüler, E
Abstract : Although histamine plays an important role in the pathophysiology of asthma through stimulation of H1 receptors, H1 antagonists are of only limited use in this disease when given orally. In order to investigate the pharmacological response to a specific H1 antagonist administered by different routes, we measured the effect of inhaled clemastine on airway responsiveness to histamine aerosol and compared the results with those after oral and intravenous administration in normal and asthmatic subjects. Inhalation of 0.6 mg clemastine provided significant protection without side effects and was comparable to intravenous administration of 1.0 mg in both groups. In normal subjects 2.0 mg clemastine orally was significantly less effective than the two other routes of administration whereas in asthmatics an enhanced reaction to histamine was observed.